THE CONTRIBUTION OF ISLAMIC PERFORMANCE ETHICS AND WORK PRODUCTIVITY ON CUSTOMER SATISFACTION PT BANK SYARIAH INDONESIA AT ISLAMIC BOARDING SCHOOL - Jauhariyah, Nur Anim; Munawir, Munawir; Oktoviyanti, Faulina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The purpose of this study was to determine the contribution of Islamic performance ethics and work productivity to PT Bank Syariah Indonesia's customer satisfaction in northern female students at Darussalam Blokagung Islamic boarding school, Banyuwangi, East Java, Indonesia. The research approach method uses quantitative associative research. The research sample was taken using a purposive random sampling technique on 50 female students. After the respondents filled out the questionnaire, then the data were analyzed using regression analysis with the help of IBM SPSS software. The results showed that the ethical variables of Islamic performance and work productivity had a significant effect on customer satisfaction of PT Bank Syariah Indonesia on northern female students at the Darussalam Islamic boarding school Blokagung Banyuwangi, East Java, Indonesia with an R2 contribution of 21.7% while the remaining 78.3% was influenced by other variables. Islamic performance ethics and work productivity in serving customers as consumers are imperative to continue to improve so as to trigger an increase in the percentage contribution to customer satisfaction as users of Islamic banking services in Indonesia.